Dynamic simulation and virtual reality in hydrology and water resources management - Teegavarapu, Ramesh S. V.; Chandramouli, Chandramouli V. (Boca Raton C R C Press, 2021)
"This covers system dynamics simulation and virtual reality modelling applied to the spatial and temporal behavior of natural and managed water resource systems, such as water demand and supply allocations, flooding, and the interactions between different types of water"--
Keywords: Watershed management -- Data processing; Water resources development -- Data processing; Hydrologic models; Virtual reality